Real-World Experience with Dolutegravir-Based Two-Drug Regimens - Collins, Bonnie; Dominguez, Megan; Pike, James; Mrus, Joseph; Mycock, Katie; Roberts, Jenna; Waller, John; Dhir, Shelly; Garris, Cindy; Riedel, David J.; Ramgopal, Moti; Ward, Douglas J.; et al. (AIDS research and treatment, 2020)
Background. Dolutegravir-based 2-drug regimens (DTG 2DRs) are now accepted as alternatives to 3-drug regimens for HIV antiretroviral treatment (ART); however, literature on physician drivers for prescribing DTG 2DR is sparse. This study evaluated treatment patterns of DTG 2DR components in clinical practice in the US. Methods. This was a retrospective chart review in adult patients in care in the US with HIV-1 who received DTG 2DR prior to July 31, 2017, with follow-up until January 30, 2018. Primary objectives of the study were to determine reasons for patients initiating DTG 2DR and to describe the demographics and clinical characteristics. All analyses were descriptive. Results. Overall, 278 patients received DTG 2DR (male: 70%; mean age: 56 years). Most patients were treatment experienced (98%), with a mean 13.5 years of prior ART. DTG was most commonly paired with darunavir (55%) or rilpivirine (27%). The most common physician-reported reasons for initiating DTG 2DR were treatment simplification/streamlining (30%) and avoidance of potential long-term toxicities (20%). Before starting DTG 2DR, 42% of patients were virologically suppressed; of those, 95% maintained suppression while on DTG 2DR. Of the 50% of patients with detectable viral load before DTG 2DR, 79% achieved and maintained virologic suppression on DTG 2DR during follow-up. There were no virologic data for 8% of patients prior to starting DTG 2DR. Only 15 patients discontinued DTG 2DR, of whom 4 (27%) discontinued due to virologic failure. Conclusions. Prior to commercial availability of the single-tablet 2DRs, DTG 2DR components were primarily used in treatment-experienced patients for treatment simplification and avoidance of long-term toxicities. Many of these patients achieved and maintained virologic suppression, with low discontinuation rates.